2014
DOI: 10.3382/ps.2013-03741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density on growth performance, carcass traits, and foot pad lesions of White Pekin ducks

Abstract: Two experiments were conducted to study the effects of stocking density on growth performance, carcass yield, and foot pad lesions of White Pekin ducks from hatch to 14 d of age (experiment 1) and from 14 to 42 d of age (experiment 2), respectively. All ducks were reared in raised plastic wire-floor pens with a pen size of 30 m(2), and males and females were mixed at a ratio of 1:1 in each pen of both experiments. In experiment 1, a total of 10,200 ducks that were 1 d old were allotted to 20 pens according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
51
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 11 publications
13
51
2
8
Order By: Relevance
“…Meanwhile, Xie et al. () concluded that the maximum stocking density in growing Pekin ducks reared on plastic wire floor pens was eight birds/m 2 to achieve improved growth performance and carcass traits. There has been little information about the effects of stocking density on meat quality of Pekin ducks, although the demand for high‐quality meat is constantly increasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Xie et al. () concluded that the maximum stocking density in growing Pekin ducks reared on plastic wire floor pens was eight birds/m 2 to achieve improved growth performance and carcass traits. There has been little information about the effects of stocking density on meat quality of Pekin ducks, although the demand for high‐quality meat is constantly increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Although in the study of Xie et al. (), the effect of sex was not examined, males are generally more influenced by stocking density (Dozier et al., ; Sun et al., ). The stocking density recommendation may be different for male ducks due to their faster growth rate than females.…”
Section: Introductionmentioning
confidence: 99%
“…The increased densities of ducks in such production systems have resulted in changes in duck behaviour with decreased duck welfare and lower meat quality. Moreover, they have resulted in greater incidence of footpad dermatitis, scratches, bruising, poorer feathering, and condemnations (Xie et al, 2014). Therefore to meet the requirements for animal welfare and food safety, appropriate production systems must be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Rata-rata bobot badan akhir itik Peking terseleksi pada umur tujuh minggu sebesar 3.287 g/ekor dan persentase bobot daging dada sebesar 13% (Pingel 2011). Rata-rata bobot badan itik Peking pada umur 42 hari mampu mencapai 3,4 kg, pertambahan bobot badan sebesar 102,6 g/hari dengan rata-rata bobot karkas sebesar 76,2% (Xie et al 2014).…”
Section: Pendahuluanunclassified
“…Dilaporkan bahwa sifat genetik yang dimiliki oleh itik Peking tidak terlepas dari proses seleksi yang intensif dan terarah sehingga kualitas produksi yang dihasilkan juga menjadi semakin meningkat. Senada dengan Adeola (2006), peneliti lainnya yaitu Pingel (2011), juga memperkuat bahwa selain faktor genetik, faktor manajemen dan kandungan gizi pakan yang sesuai sangat berpengaruh terhadap performa bahkan terhadap kualitas karkas itik Peking (Xie et al 2014;Dozier et al 2008). Hasil penelitian ini juga memperlihatkan bahwa rata-rata bobot hidup itik PMp berbeda tidak nyata dengan itik E-PMp selama pemeliharaan enam minggu, walaupun itik PMp mewarisi sifat genetik yang berasal dari indukannya yakni itik Peking sebagai salah satu itik tipe itik pedaging yang terkenal.…”
Section: Pengaruh Ransum Perlakuan Terhadap Bobot Badan Hidup Itikunclassified